Ascomycetes from the relic forest of Oreomunnea mexicana, Oaxaca, Mexico - Valenzuela, Ricardo; Raymundo, Tania; Reyes, Pamela; Guzmán-Guillermo, Jorge; Acosta, Salvador; Ramírez-Martínez, Julio Cesar; Luna-Vega, Isolda (Phytotaxa, 2021)
La Esperanza is an Oaxacan relic area of the Tertiary, dominated by the big tree Oreomunnea mexicana (Juglandaceae). The forest is part of the priority region for the conservation of La Chinantla and constitutes one of the most conserved Mexican tropical montane cloud forests. We studied the Ascomycetes fungi and found 63 species, of which 32 are new records for Oaxaca. Ascocoryne inflata, Calyculosphaeria macrospora, Cercophora costaricensis, Chaetosphaeria ellisii, Coccomyces limitatus, Lasiosphaeria ovina, Leptogidium dendriscum, Marthamyces quadrifidus, Stereocaulon didymicum and Thelonectria lucida are new records for Mexico. Xylaria was the most diverse genus with 12 species. The most abundant species were Xylaria arbuscula and Lachnum apalum. The main growth habit was lignicolous. The tropical montane cloud forest of La Esperanza has unique characteristics allowing great taxonomic diversity of Ascomycetes.